THE RISK OF FINANCIAL NETWORKS IN THE CONTEXT OF CURRENT CHALLENGES - MANTA, Otilia (Economy and Sociology, 2021)
In the current context of the redefinition of financial markets due to the challenges generated by the multi-polarity phenomenon, virtual space becomes the main trading place for financial products, and our role as a researcher is to identify new financial instruments appropriate to this reality, which is why we consider that a market trend financial is that of a new network architecture in the virtual financial space based on nodes of financial interference. Moreover, financial space is a monetary representation of all other areas that can be identified and defined in society, especially in the economy, and can be considered as a set of specific financial interconnections with defining characteristics that determine them. Along with the profound changes in the interconnection of the socio-economic entities, using the new information channels, more and more often in the discussions of the specialists and not only a number of monetary issues are debated, in its virtual aspect, respectively the financial risks related to the virtual space, as well as the degree of “mastery” of information networks. In this context, in this paper we will try to make a series of contributions on how this financial space is designed – as a complex network with an adequate degree of risk.